End user experiences of an electronic health records platform in a tertiary hospital system in Kenya - Anmol Shrestha; Jasmit Shah; Zamanali Khakhar; Armando Ruiz; Zohray Talib; Sayed K. Ali (PLoS ONE, 2025)
Background Electronic Health Record (EHR) systems allow health care facilities to provide better care to patients and improve overall provider efficiency. They are vital for low-and middle-income countries in achieving the United Nations Sustainable Development Goal of ensuring healthy lives and promoting the well-being of all their citizens. This study aimed to evaluate perceptions and usage of a comprehensive EHR by end-users after its deployment into a tertiary hospital system and its outpatient centers in Kenya and also aimed to understand the effectiveness of various implementation strategies deployed by the institution during their implementation process. Methods We conducted a cross-sectional study between October 2023 and January 2024 at the Aga Khan University Hospital, Nairobi with staff involved in using the EHR system. A standardized electronic questionnaire was shared with the users and responses were captured on REDCap after obtaining written consent electronically. Results Of the 548 participants who agreed to join the study, 471 responded to the survey in full. Most respondents (420, 89.9%) stated that the EHR made their work better or much better, compared to a paper-based system. Majority of end-users stated that the EHR benefited their practice (378, 87.1%), provided autonomy to healthcare workers (382, 86.2%), the quality of healthcare (424, 95.5%), interactions within the healthcare team (353, 79.1%) and enjoyment of their clinical practice (360, 80.7%). Conclusion The majority of end users believed the EHR to be effective and appropriate to use within this specific and unique healthcare system. The specific strategies deployed by institution were also successful in ensuring high rates of EHR usage and can be looked at as a blueprint for future EHR deployments in other sub-Saharan African healthcare systems.